Konsep Marketing Berbasis Maqoshid Al-syari'i Imam Al-Ghazali - Ivan Rahmat Santoso (ITB AAS INDONESIA Surakarta, 2019)
The thinking of the Imam Al-Ghazali socioeconomic Ra stem from a concept he called